Islam dan kesejahteraan antara representasi dan inspirasi dalam demokrasi: Islam and welfare between representation and inspiration in democracy - Sulaiman, Surpani; Anshor, Maria Ulfah (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2023)
Social welfare is often measured based on aspects such as income, population, health, education, employment, consumption, housing, and social culture. However, some people who already have a luxurious house, vehicle, deposit, and various other forms of wealth actually feel anxious, restless, fearful, and even commit suicide. This fact shows that there is something lacking in measuring social welfare. Islamic economics offers a different concept of welfare. Welfare in Islam is not only measured from the material aspect, but also from the spiritual aspect. In Islam, the happiness of life is given by Allah SWT to anyone who is willing to do good deeds accompanied by faith in Allah SWT. Three indicators for measuring welfare and happiness in Islam are mental formation (tauhid), consumption, and the disappearance of fear and all forms of anxiety. Zakat is one of the important instruments in Islamic economics to achieve social welfare. Zakat is an obligation for every Muslim who is able to give out a portion of his wealth to be given to those in need. Zakat can make a significant contribution to the economy of society, especially for rural communities. Zakat can also help reduce poverty and social inequality. By applying the concept of welfare offered by Islam, we can create a prosperous society, both materially and spiritually.